The current 'upswing' in the South African economy and the international capitalist crisis: A reinterpretation of South African 'development' - Kaplan, D. (My University, 1981)
This paper attempts to situate the current economic ‘upswing’ in the South African economy in the context of the on-going economic crisis which is plaguing the international capitalist economy. I will argue that the two phenomena are integrally linked. The principal features of the international capitalist crisis and, even more centrally, the measures hitherto taken to resolve this crisis, are the principal factors contributing to the present ‘upswing’ in the South African economy
African Studies Seminar series. Paper presented 27 April, 1981